Manajemen Pendidikan di Masa Pandemic Corona Virus Disease 19 (Studi Empirik pada SMK Kesehatan Bhakti Kencana Subang) - Sugiyana, Yogi; Iriantara, Yosal; Handayani, Sri (Jurnal Manajemen & Pendidikan [JUMANDIK], 2024)
Corona Virus Disease 2019 (COVID-19) was first discovered in the city of Wuhan, China at the end of December 2019. This virus spreads very quickly and has spread to almost all countries, including Indonesia, in just a few months. So that on March 11, 2020 WHO declared this outbreak a global pandemic. Covid-19, all business management systems, businesses, entrepreneurship are paralyzed, also in education, the management managemen system must change the way it works and the system can be used and run according to the provisions so that quality can be met. Some governments have decided to implement a policy for student holidays and start implementing online learning methods (online) or online. for several schools in each region. These schools are not ready with an online learning system, which requires learning media such as mobile phones, laptops, or computers. Teachers must ensure that teaching and learning activities continue, even though students are at home. The solution is that teachers are required to be able to design learning media as innovations by utilizing online media (online). The use of several applications in online learning is very helpful for teachers in this learning process. Teachers must be accustomed to teaching by utilizing complex online media that must be packaged effectively, easily accessible, and understood by students. In that case, how does managerial education in the education unit manage learning during the covid19 pandemic?, what kind of educational management is needed and must be developed? This research will be conducted at the locus at the Bhakti Kencana Health Vocational School in Subang which is a vocational high school with the health sector. so you can see what kind of management is being developed.